2019
DOI: 10.7554/elife.44235
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of microenvironmental metabolites in murine cancers reveals determinants of tumor nutrient availability

Abstract: Cancer cell metabolism is heavily influenced by microenvironmental factors, including nutrient availability. Therefore, knowledge of microenvironmental nutrient levels is essential to understand tumor metabolism. To measure the extracellular nutrient levels available to tumors, we utilized quantitative metabolomics methods to measure the absolute concentrations of >118 metabolites in plasma and tumor interstitial fluid, the extracellular fluid that perfuses tumors. Comparison of nutrient levels in tumor int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
424
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 434 publications
(443 citation statements)
references
References 110 publications
16
424
1
2
Order By: Relevance
“…Previous studies have found cystine levels to be limiting in the PDA microenvironment. Cysteine was shown to be the second most depleted amino acid in pancreatic tumors relative to adjacent healthy pancreatic tissue 23 and the levels of cystine in PDA tumor interstitial fluid (~50μM) which is 2-fold lower than in plasma taken from the same tumor-bearing mice 24 . Based on these observations, we sought to test the effect of GOT1 knockdown under physiological concentrations of cystine.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have found cystine levels to be limiting in the PDA microenvironment. Cysteine was shown to be the second most depleted amino acid in pancreatic tumors relative to adjacent healthy pancreatic tissue 23 and the levels of cystine in PDA tumor interstitial fluid (~50μM) which is 2-fold lower than in plasma taken from the same tumor-bearing mice 24 . Based on these observations, we sought to test the effect of GOT1 knockdown under physiological concentrations of cystine.…”
Section: Resultsmentioning
confidence: 97%
“…When GOT1 is inhibited, NADPH availability is decreased and GSH cannot be sufficiently regenerated by reducing GSSG. This metabolic rewiring could be exploited by dietary means, which has a major influence on the nutrient composition within pancreatic tumors 24 . This result adds to a growing body of literature indicating how the metabolic environment can influence sensitivity to therapy 48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…5 Later in his life, he changed his side of view and claimed that tumor cells are characterized by a damaged respiration. 6,7 In contrast to these observations and numerous studies since, two recent publications stated that the tumor environment contains no elevated lactate levels in the interstitial fluid, 8,9 and lactate may accumulate preferentially in tumor cells. In this case, the tumor stroma, for example, immune cells, would not face high-lactate concentrations.…”
Section: His Toric Al Timeline-the Warburg Effec T Then and Nowmentioning
confidence: 86%
“…more common dietary modifications that alter the ratios and/or amounts of carbohydrates, proteins, and fats might alter tumor growth via effects on tumor nutrient availability is poorly understood, and one framework for examining the impact of diet on tumor metabolism is to consider how dietary factors modulate the systemic availability of nutrients that are available for use by cancer cells within a tumor 1 . Perturbations to dietary compositions can change metabolite levels in circulation, which in turn can influence metabolite levels in the tumor microenvironment 3 . Thus, diet-induced changes in nutrient availability could affect how cancer cells utilize these nutrients to support cell proliferation, thereby altering tumor growth, progression, and/or response to therapy.…”
mentioning
confidence: 99%
“…To determine how nutrient availability in tumors is differentially affected by each diet, we measured the levels of several metabolites in the plasma and tumor interstitial fluid (TIF) harvested from tumor-bearing mice fed a control diet, the CR diet, or the KD. TIF comprises of the fluid surrounding cancer cells within the tumor microenvironment, and therefore may better reflect the nutrient environment to which cancer cells are exposed in tumors 3 . For example, despite lowering blood glucose levels, the KD does not lower glucose levels in TIF (~2.8 mM for both control and KD), whereas a decrease in TIF glucose levels from ~1.6 mM to ~0.8 mM is observed when mice are exposed to CR ( Fig.…”
mentioning
confidence: 99%